Influência das fases hídricas e tipos de substratos artificiais sobre as larvas de Chironomidae, no trecho superior do rio Paraná. - Anjos, Adriana Félix dos (2007)
This study is linked to the Project entitled "Benthic community from alluvial floodplain of Upper Paraná River, with emphasis on Bivalvia" (Productivity scholarship/ CNPq- Proc. 303850/2005-1) and aimed to verify the influence of hydrological phases on Chironomidae larvae in different substrate types. The second goal was to identify the main food items eaten by Cricotopus sp. and compare possible differences on the larvae diet from different artificial substrates and hydrological phases. We used four types of artificial substrates: wood X-shaped (MADX); nitacetal plates X-shaped (NITX); PVC tube-shaped (PVCT) and galvanized metal tube-shaped (METT), each one with three replicates. Samplings were undertaken fortnightly, between August 2004 and December 2005. The material was collected using spatula and brush and a 5x5 cm square (0.0025 m2). Seventeen Chironomidae morphospecies were identified and Cricotopus sp. was dominant in most of substrates and hydrological phases. During low water phase, the highest similarity was observed among substrates with the same shape. In this period, the highest species richness and density of larvae were registered in substrates X-shaped, probably due to the high accumulation of organic matter in MADX and PVCX substrates. During high water phase, the increase in fluviometric level of Paraná River influenced on the reduction of larvae mean density and, only in MADX and PVCT substrates, whose materials favored the best larvae fixing, high values of density were verified. Regarding the Cricotopus sp. diet, detritus was the main food item, with values above 50% from the total consumption. In the digestive content of Cricotopus sp. larvae, we observed the predominance of algae genera as the water phases, with significant differences in the larvae diet at PVCT substrate. In this substrate, Cricotopus sp. ingested low quantity of detritus and high percentage of diatoms. The results indicated that hydrological phases of Paraná River can influence the diet of Cricotopus sp. larvae, suggesting that this is an opportunistic genus that feeds on available resources.